2000
DOI: 10.1053/he.2000.5790
|View full text |Cite
|
Sign up to set email alerts
|

Fractional allelic loss in non-end-stage cirrhosis: Correlations with hepatocellular carcinoma development during follow-up

Abstract: Hepatocellular carcinoma (HCC) is usually preceded by cirrhosis whose genetic background is still poorly understood. The aim of this study was to evaluate, in non-endstage cirrhosis, the fractional allelic loss (FAL) at loci mostly reported to be altered in HCC and the microsatellite instability (MSI). Twenty cases of cirrhosis were retrospectively selected. Eleven had developed an HCC during the follow-up (HCC-prone group), while 9 remained HCC-free (HCC-free group). Microdissected hepatocellular cirrhotic no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 30 publications
1
18
0
Order By: Relevance
“…Indeed we found that most cirrhoses and the vast majority of malignant tumors had promoter methylation affecting at least a single gene. Thus, in addition to well-recognized molecular abnormalities such as loss of heterozygosity, deletion, and point mutation, [16][17][18][19][20] inactivation of cell cycle inhibitors by epigenetic mechanisms seems to play an important role in human hepatocarcinogenesis. We have also found that methylated cirrhosis usually associates to methylated HCC, suggesting a common mechanism of gene inactivation from cirrhosis to HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed we found that most cirrhoses and the vast majority of malignant tumors had promoter methylation affecting at least a single gene. Thus, in addition to well-recognized molecular abnormalities such as loss of heterozygosity, deletion, and point mutation, [16][17][18][19][20] inactivation of cell cycle inhibitors by epigenetic mechanisms seems to play an important role in human hepatocarcinogenesis. We have also found that methylated cirrhosis usually associates to methylated HCC, suggesting a common mechanism of gene inactivation from cirrhosis to HCC.…”
Section: Discussionmentioning
confidence: 99%
“…This position appears partially conservative, and others have questioned whether it was appropriate to continue using dinucleotide markers for the purpose of MSI identification (Laghi et al, 2004). Furthermore, the appropriate use of mononucleotide markers was instrumental in ruling out MSI as a frequent cancer phenotype in organs other than the colon, in which it was improperly assessed merely by taking advantage of dinucleotide microsatellites used for LOH assessment (Roncalli et al, 2000). Taking for granted that using BAT26 alone might lead to some (unknown) underestimation of the true MSI, owing to the non-recognition of the cases with biallelic hMSH2 deletion, we screened by this marker probably the largest mono-institutional series of consecutive surgically resected CRCs and found a 10% MSI prevalence (Malesci et al, 2007).…”
Section: Improving the Standards For Msi Identification By Evaluatingmentioning
confidence: 99%
“…Hepatocellular carcinoma (HCC) is the most common primary malignant tumor of the liver and the fourth most common cause of cancer-related death in the world [1] . Male predominance is, however, more obvious in populations at high risk of developing this tumor (mean ratio 3.7:1.0) than in those at low or intermediate risk (2.4:1.0) [2] .…”
Section: Introductionmentioning
confidence: 99%